#### Answer

$\dfrac{\dfrac{4y-8}{16}}{\dfrac{6y-12}{4}}=\dfrac{1}{6}$

#### Work Step by Step

$\dfrac{\dfrac{4y-8}{16}}{\dfrac{6y-12}{4}}$
Evaluate the division:
$\dfrac{\dfrac{4y-8}{16}}{\dfrac{6y-12}{4}}=\dfrac{4y-8}{16}\div\dfrac{6y-12}{4}=\dfrac{(4)(4y-8)}{(16)(6y-12)}=...$
Take out common factor $4$ from the second parentheses in the numerator and common factor $6$ from the second parentheses in the denominator. After that, simplify:
$...=\dfrac{(4)(4)(y-2)}{(16)(6)(y-2)}=\dfrac{16}{(16)(6)}=\dfrac{1}{6}$